Decreasing Trauma Readmission Rates by Implementing a Callback Program. Issue 1 (January 2019) - Bath, Jennifer; Freeman, Daniel; Salamoun, Mariana; Harvey, Ellen; Wright, Andrea; Hamill, Mark; Lollar, Daniel; Love Bower, Katie; Collier, Bryan
Abstract : Decreasing hospital lengths of stay increases the burden on trauma patients after discharge. Our hypothesis was that a discharge callback protocol would decrease readmission rates. A retrospective quality improvement study evaluated all trauma patients admitted from 2012 to 2016 at a Level I trauma center. A postdischarge callback protocol was implemented in 2014, with a mature protocol in place in 2015. The precall and callback groups were compared regarding demographics, injury severity, and trauma readmission. Callback data included length of call, unsolicited patient comments, and education provided. Chi-square and Fisher's exact tests were used to compare categorical variables, whereas an independent-samples t test was used to compare continuous data. The precall program group included 4, 470 admissions, and the call program group included 4, 647 admissions. The precall program group had a higher injury severity score (ISS; 11.7 vs. 10.3; p < .001) and fewer males (62% vs. 65%, p = .002). In the call program group, there was a significant decrease in readmission rates (1.42% vs. 0.81%; p = .04). Patients with an unplanned readmission had a higher ISS (14.9 vs. 11.0, p < .01), a longer mean hospital length of stay during initial admission (9.3 days vs. 4.8 days, p < .01), and were more often discharged to locations with medical oversight (37.4% vs. 26.7%, p = .03). Of the patients in the call program group, 27.9% were reached. An average of 5.8 ± 2.9 min per call was calculated, equating to a 0.2 full-time equivalent. A discharge callback program for approximately 2, 500 trauma patients per year leads to fewer readmissions, which financially supports the callback position.